2022
DOI: 10.1016/j.jse.2021.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff repair using a bioresorbable nanofiber interposition scaffold: a biomechanical and histologic analysis in sheep

Abstract: Background: The purpose of this study was to evaluate the mechanical, structural, and histologic quality of rotator cuff repairs augmented with an interposition electrospun nanofiber scaffold composed of polyglycolic acid (PGA) and poly-L-lactide-co-ε-caprolactone (PLCL) in an acute sheep model. Methods: Forty acute infraspinatus tendon detachment and repair procedures were performed in a sheep infraspinatus model using a double-row transosseous-equivalent anchor technique either with an interposition nanofibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Also, the tendon-bone attachment at 12 weeks histologically appeared more like native fibrocartilaginous insertion with prominent perforating collagen fibers. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the tendon-bone attachment at 12 weeks histologically appeared more like native fibrocartilaginous insertion with prominent perforating collagen fibers. 28 …”
Section: Discussionmentioning
confidence: 99%
“…The scaffold has a microporous nature, which, combined with the structure of the nanofibers, is the likely mechanism through which the scaffold promotes a healing response similar to that of native tissue. 1 , 22 In a recent sheep study, Romeo et al 28 demonstrated that the inclusion of the nanofiber scaffold significantly increased the strength of rotator cuff repair and produced more Sharpey fiber–like attachments at the enthesis at 3 months compared with repairs without scaffold augmentation. Specifically, incorporation of the scaffold into rotator cuff repair increased the ultimate failure force by 47% at 12 weeks compared with suture anchors alone.…”
mentioning
confidence: 99%
“…They have greater mechanical strength, better mechanical properties and better degradation rates in vivo than natural polymer materials [ 65–68 ]. Among these commonly used polymers, PCL has the slowest degradation rate, followed by PLA [ 69 ] and polyglycolide acid (PGA) [ 70 ]. In contrast, Poly (lactic-co-glycolic acid) (PLGA) has the fastest degradation rate [ 71 ].…”
Section: Products Of Tendon and Ligament Reconstruction And Repairmentioning
confidence: 99%
“…The FTE field has seen exciting research in: (1) developmental biology to learn how tissues form and grow (e.g., Brown et al, 2015;Glass et al, 2014); (2) novel biomaterials as carriers of autologous and allogeneic cells (Marturano et al, 2016;Ratcliffe et al, 2015;Romeo et al, 2022); and (3) sophisticated bioreactors to mature TECs (e.g., Butler et al, 2009). These publications over the past decade are too F I G U R E 1 0 A functional tissue engineering (FTE) "road-map" to describe steps in the in vitro tissue engineering (above the line) as well as in vivo surgery and evaluation phases (below the line).…”
Section: Developmental Biology Biomaterials and Bioreactorsmentioning
confidence: 99%